"A bad, bold, big-nosed, biblical brother": refashioning the funny Jew in post-World War Two America. Issue 1 (2nd January 2017) - Tanny, Jarrod
ABSTRACT: Film director Jonathan Kesselman's 2003 comedy The Hebrew Hammer introduced a new Jewish superhero on cable television: a tough, hip, jive-talking "biblical brother" who battles anti-Semites on the streets of New York under the gaze of adoring children, desirous women, and admiring African-Americans. Although the Hebrew Hammer is a cool Jewish thug who transcends the exilic condition of the proverbially submissive diaspora Jew through his brawn and swagger, he is also funny; he is a gangster who exhibits the neuroses, complaints, and schlemiel-like stereotypes that lie at the heart of modern Jewish humour. The Hebrew Hammer represents the culmination of a trend in American popular culture that began in the 1950s with Lenny Bruce. An unapologetically proud Jew, Bruce deployed his comedy and his cool persona to demolish Gentile propriety. Proclaiming an affinity to other minorities who had also suffered at the hands of Anglo-Saxon Christendom, Bruce and his successors publicly mocked their history of exclusion and the legacy of racism. A narrative of shared affliction has allowed Jewish humourists to appropriate the stereotypes and cultural practices of African-Americans and other ethnic groups, and to embed them into their comedy, fusing them with familiar Jewish tropes. This is the foundation of a new Jewish humour, one that remains anchored in the past, even as it has been refashioned to suit a multi-cultural immigrant society.